Identification of disulfidptosis-related prognostic biomarkers associated with CD4 + and CD8 + T cells infiltration for sarcoma by integrating bioinformatic analysis and experimental validation - Wenliang Tan; Xi Zhou; Ting Wang; Shuanghua Wu; Ting Mo; Zhiqin Xie; Yang Xie (Discover Oncology)
Abstract Recently identified, disulfidptosis represents a novel form of cell death triggered by disulfide stress. The impact of disulfidptosis-related gene (DRG) patterns on the clinical prognosis of sarcoma, however, remains unexplored. In this study, two prognostic genes related to DRGs, CCDC69 and HMGB3, were found, and a prognosis prediction models of sarcoma subtypes was developed. KM and AUC analysis revealed the remarkable prediction accuracy of these models. CCDC69 and HMGB3 are differentially expressed, which is closely related to survival results and the existence of a large number of immune infiltrating cells in cancers. The mIHC analysis showed that compared with normal tissues, the levels of HMGB3 in sarcoma tissues was higher, and the high expression of HMGB3 was related to the increased infiltration of CD4 + and CD8 + T cells. This study reveals the potential of combining CCDC69 and HMGB3 with DRGs as a new biomarker for the clinical diagnosis and a potential immunotherapy targets for sarcoma.